(untitled) (Academia Journal of Medicine, 2018)
Background: Tuberculous pleural effusion (TPE) is very common in developing countries in comparison of developed countries; further TPE is one of the common characteristic of extra pulmonary tuberculosis. Adenosine deaminase (ADA) is an important enzyme which is found highly active in the diseases which induce cellular immunity. Therefore, the present study was designed to evaluate the accuracy of ADA level in the diagnosis of pleural effusion caused by tubercular etiology. Subjects and Methods: This was a cross-sectional type of study conducted at tertiary care institute. Total one hundred thirty five patients of pleural effusion were recruited for the study among them eighty nine pleural effusion patients were suffering with tuberculosis and forty six pleural effusion patients were without tuberculosis. A p-value < 0.05 was considered statistically significant. IBM SPSS Statistics 21 manufactured by IBM USA was used for entire calculations. Results: Findings of the present study have shown there was significant difference between ADA level of tubercular effusion patients (69.3±27.22) in comparison of non-tubercular pleural effusion patients (20.46±7.34). Further there was a significance difference between Lactate dehydrogenase (LDH) levels of the tubercular effusion patients (172.72±25.7) in comparison of non-tubercular pleural effusion patients (81.91±6356). However there was no significance difference between total protein (p>0.05), glucose level (p>0.05) and total cells (p>0.05) level of both groups. Conclusion: Finding of the present study showed that The ADA level was significantly high in pleural effusion patients with tubercular etiology in comparison of non-tubercular pleural effusion.